PEDİYATRİK KAUDAL BLOKTA ROPİVAKAİNE EKLENEN KETAMİNİN ETKİNLİĞİ - ÖDEŞ, RAMAZAN (Fırat Üniveristesi, 2006)
İnguinal bölge operasyonu geçirmesi planlanan çocuklarda kaudal anestezideropivakainin ve ropivakaine eklenen ketaminin, anestezi yeterliliği, hemodinamikparametreler ve postoperatif ağrı tedavisindeki etkinliklerini karşılaştırdık.Gereç ve Yöntem: Çalışmamıza fakülte etik kurul ve ailelerin onayı alınan ASA 1-2grubundan 1-4 yaşlarında inguinal girişim planlanan 45 olgu alındı.Anesteziindüksiyonu yüz maskesi yolu ile % 50 O2/% 50 N2O karışımı içinde % 8konsantrasyonda sevofluran ile yapıldı. Tüm hastalara vekuronyum (0.1 mg kg-1) ileyeterli kas gevşekliği sağlanarak, kafsız tüp ile endotrakeal entübasyon uygulandı.Anestezi idamesi % 50 O2/% 50 hava karışımı içinde % 0.5-2.5 konsantrasyondasevofluran ile sürdürüldü. Hastalarımız rastgele 3 gruba ayrıldı. Grup R'ye 2 mg kg-1% 0.2 ropivakain, Grup K'ye 0.5 mg kg-1, ketamin, Grup R+K'ye 2 mg kg-1, % 0.2ropivakain+0.5 mg kg-1 ketamin kaudal olarak verildi.Hastalarımızın ağrı düzeyleri modifiye CHEOPS ile, sedasyon durumu Wilsonsedasyon skalası kullanılarak, postoperatif dönemdeki motor aktivite derecesi 3-nokta skalayla değerlendirildi. Verilerin istatistiki değerlendirmesinde SPSS 12.0paket programı kullanıldı.Bulgular: Grupların yaş, ağırlık, operasyon türleri arasında fark saptanmadı(p>0.05). Modifiye CHEOPS skorunun, postoperatif 45. dakikada R grubunda , K veR+K grubuna göre istatistiksel olarak anlamlı artmış olduğu bulundu (p<0.05).Modifiye CHEOPS skorunun R grubunda, R+K grubuna göre 60. dakikadaistatistiksel olarak anlamlı artmış olduğu saptandı (p<0.05). K (852Â±309 dakika) veR+K grubunda (1032Â±270 dakika), ropivakain grubuna (435.6Â±273 dakika) göreanaljezi süresinin istatistiksel olarak anlamlı uzun olduğu saptandı (p<0.05).Analjezik gereksiniminin 24 saat içindeki değerlendirilmesinde analjezik gereksinimiolan olgu sayısının R+K grubunda daha az olduğu belirlendi. Sedasyon skorları tümgruplarda <2 seyretti. R ve K grubunda ikişer hastamızda bulantı ve kusma, Rgrubunda 1 hastamızda idrar retansiyonu, K grubunda 2 ve R+K grubunda 1hastamızda hallüsinasyon, K grubunda 3 ve R+K grubunda 1 hastamızda nistagmusgözlendi.Sonuç: Çocuklarda kaudal ropivakain, ketamin ve ropivakain+ketamin ile etkin birpostoperatif analjezinin sağlandığı, ropivakaine eklenen ketaminin analjezi süresiniuzattığı ve daha az analjezik gereksinimi doğurduğu anlaşıldı.Anahtar kelimeler: Kaudal blok, ropivakain, ketamin, postoperatif ağrı.

The effect of ketamine adding to ropivacaine on the caudal block inpediatric anesthesiaThe aim of this study was to identify the effectiveness of ropivacaine andropivacaine plus ketamine on the efficiency of anesthesia, haemodynamic parametersand the treatment of postoperative pain in pediatric patients were planned to performoperations for inguinal region.Materials and Methods: Forty-five patients with ASA score 1-2, between ages 1 to4 were enrolled to study approved by local ethic committee and by their family.Induction of anesthesia was performed via face mask with sevoflourane 8 % in 50 %O2 / 50% N2O mixture. Vecuronium was used to all subjects in dose of 1 mg kg-1 foradequate relaxation of muscles and intratracheal intubation was performed with tubewithout cuff. Maintenance dose of anesthesia was provided with sevoflourane 0.5-2.5% in 50 % O2 / 50% air mixture. Patients were randomly divided into 3 groups.Ropivacaine 0.2% 2 mg kg-1 was given to Group R via caudally, ketamine 0.5 mg kg-1was given to Group K via caudally and Ropivacaine 0.2% 2 mg kg-1 plus ketamine0.5 mg kg-1 was given to Group R+K via caudally.The degree of pain, the condition of sedation and the degree of motor activity in thepostoperative period were evaluated with Modified CHEOPS, Wilson sedation scaleand three point scale, respectively. SPSS 12.0 for windows was performed for theevaluation of statistically significance.Results: There were no differences between groups for ages, weight and types ofoperations. Modified CHEOPS scores were found to be significantly higher inpostoperative 45th minute in Group R compared with others (p<0.05). Similarly thisscore was found to be higher in postop. 60th minute in Group R compared withGroup R+K (p<0.05). The duration of analgesia was significantly longer in Group K(852±309 min) and Group R+K (1032±270 min) than Group R (435.6±273 min)(p<0.05). The necessity of analgesic medication was significantly found to be lowerin Group R+K in 24 hours following operations. The scores of sedations were <2 inall groups. Nausea and vomiting were noted in two patients in both Group R and K,urinary retention was noted in only one patient in Group R, hallucination wasconsidered in two patients in Group K and in one patient in Group R+K, and finallynistagmus was determined in three patients in Group K and one patient in GroupR+K.Conclusion: It was concluded that caudally administered ropivacaine, ketamine andropivacaine + ketamine were found to be an effective on postoperative analgesia inpediatric patients. Moreover ketamine adding to ropivacaine was considered toprolong the duration of analgesia and to reduce the postoperative analgesiarequirement.Key words: Caudal block, ropivacaine, ketamine, postoperative pain.
The Effect of Ketamine Adding to Ropivacaine on the Caudal Block in Pediatric Anesthesia
Keywords: Anestezi ve Reanimasyon